2008
DOI: 10.21704/rea.v7i1-2.353
|View full text |Cite
|
Sign up to set email alerts
|

Condiciones Meteorológicas Y Dinámica Vegetal Del Ecosistema Costero Lomas De Atiquipa (Caravelí – Arequipa) en El Sur Del Perú

Abstract: ResumenLos ecosistemas costeros de Lomas están constituidos por comunidades vegetales desarrollándose bajo influencia de neblinas invernales. Para explorar este enunciado se determinó la relación entre las condiciones meteorológicas y la dinámica vegetal en las Lomas de Atiquipa, cerros Barrera y Lagunillas (15º46' LS y 74º22' LO, a 800 msnm aprox) entre Febrero 2005 y Febrero 2006. En cada cerro se instalaron 45 parcelas de 0.5 x 0.5 m; evaluándose mensualmente por parcela el número de especies e individuos p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 4 publications
0
12
0
3
Order By: Relevance
“…For example, long-term monitoring studies (≥ 5 years) in the west of the Dead Sea [ 54 ] and the Chihuahuan desert [ 55 ] found the same positive correlation. However, no such correlation was found in a study in southern Peru (Lomas de Mejia) over a one-year monitoring [ 38 ]. Instead, our colleagues found a positive correlation between Shannon diversity and water collected from fog [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, long-term monitoring studies (≥ 5 years) in the west of the Dead Sea [ 54 ] and the Chihuahuan desert [ 55 ] found the same positive correlation. However, no such correlation was found in a study in southern Peru (Lomas de Mejia) over a one-year monitoring [ 38 ]. Instead, our colleagues found a positive correlation between Shannon diversity and water collected from fog [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, no such correlation was found in a study in southern Peru (Lomas de Mejia) over a one-year monitoring [ 38 ]. Instead, our colleagues found a positive correlation between Shannon diversity and water collected from fog [ 38 ]. Our study did not implement fog collection measurements, but previous studies found substantial fog contribution in Lomas de Lachay [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 'Lomas' are environments of evergreen scrubs specialized in the capture and retention of water from oceanic mist (Ferreyra, 1983;Morello, 1985;Zeballos et al, 2000;Aragón and Aguirre, 2014). In many areas, this mist is the only source of water (Ferreyra, 1983;Morello, 1985;Zeballos et al, 2000;Sotomayor Melo and Jiménez Milón, 2008). These particular environments allow the presence of a few bats species that live in otherwise extreme climatic conditions; H. ma crotus has been cited among them Aragón and Aguirre, 2014).…”
Section: Biogeographic Approximations and Climatic Determinantsmentioning
confidence: 99%
“…de Piura (6º L.S.) hasta el norte de Chile en la ciudad de Coquimbo (30º LS), presentándose en forma más intensa entre los 8º y 18º LS (Rundel et al, 1991;Sotomayor & Jiménez, 2008;Velasquez, 2014). Se desarrollan desde la línea del mar hasta los 1 000 msnm, abarcando un territorio de 3 500 km y con una distribución exclusiva para Sudamérica; en Perú se tiene un área de 2 000 km² de estas formaciones vegetales (Sotomayor & Jiménez, 2008).…”
Section: Introductionunclassified